Identification and Functional Characterization of a Geraniol Synthase UrGES from Uncaria rhynchophylla - Xinghui Liu; Wenqiang Chen; Linxuan Li; Detian Mu; Iain W. Wilson; Xueshuang Huang; Yahui Xiang; Lina Zhu; Limei Pan; Deyou Qiu; Qi Tang (Plants)
Uncaria rhynchophylla, a medicinal plant extensively used in traditional Chinese medicine, is an important plant source of terpenoid indole alkaloids (TIAs), but the mechanism of TIA biosynthesis at molecular level remains unclear. Geraniol synthase (GES) serves as a crucial enzyme in catalyzing the formation of geraniol from geranyl pyrophosphate (GPP) in various plants, but the functional characterization of the GES gene in U. rhynchophylla has not been investigated. In this study, a GES was identified and characterized through genome mining and bioinformatic analysis. Functional validation was performed via a protein catalysis experiment, transient expression in Nicotiana benthamiana, and methyl jasmonate (MeJA) induction experiments. The full-length UrGES gene was 1761 bp, encoding a protein product of 586 amino acids with an estimated 67.5 kDa molecular weight. Multiple sequence alignments and phylogenetic analysis placed UrGES within the terpene synthase g (TPS-g) subfamily, showing high similarity to known GESs from other plants. Enzymatic assays confirmed that recombinant UrGES catalyzed GPP conversion to a single product of geraniol. The transient expression of UrGES resulted in geraniol accumulation in N. benthamiana, further confirming its function in vivo. UrGES expression was observed in leaves, stems, and roots, where leaves had the highest transcript levels. Moreover, MeJA treatment significantly upregulated UrGES expression, which positively correlated with an increase in alkaloid content. This study functionally characterizes UrGES as a geraniol synthase in U. rhynchophylla, contributing to the current knowledge of the TIA biosynthetic pathway. These findings may offer insights for future metabolic engineering aiming to enhance TIA yields for pharmaceutical and industrial applications.